The Medicare Hospital Readmissions Reduction Program: Potential Unintended Consequences for Hospitals Serving Vulnerable Populations. (13th January 2014) - Gu, Qian; Koenig, Lane; Faerberg, Jennifer; Steinberg, Caroline Rossi; Vaz, Christopher; Wheatley, Mary P.
<x xml:space="preserve">Abstract</x> Objective To explore the impact of the Hospital Readmissions Reduction Program (HRRP) on hospitals serving vulnerable populations. Data Sources/Study Setting Medicare inpatient claims to calculate condition‐specific readmission rates. Medicare cost reports and other sources to determine a hospital's share of duals, profit margin, and characteristics. Study Design Regression analyses and projections were used to estimate risk‐adjusted readmission rates and financial penalties under the HRRP. Findings were compared across groups of hospitals, determined based on their share of duals, to assess differential impacts of the HRRP. Principal Findings Both patient dual‐eligible status and a hospital's dual‐eligible share of Medicare discharges have a positive impact on risk‐adjusted hospital readmission rates. Under current Centers for Medicare and Medicaid Service methodology, which does not adjust for socioeconomic status, high‐dual hospitals are more likely to have excess readmissions than low‐dual hospitals. As a result, HRRP penalties will disproportionately fall on high‐dual hospitals, which are more likely to have negative all‐payer margins, raising concerns of unintended consequences of the program for vulnerable populations. Conclusions Policies to reduce hospital readmissions must balance the need to ensure continued access to quality care for vulnerable populations.